The Role of Hand Surgery on Quality of Life and Patient Satisfaction in Rheumatologic Patients - Uğur Bezirgan; Mehmet Yalçın (Ankara Üniversitesi Tıp Fakültesi Mecmuas, 2025)
Objectives: Rheumatologic diseases, particularly rheumatoid arthritis (RA), often lead to hand and wrist dysfunction, significantly impairing patients’ quality of life. Despite advancements in pharmacotherapy, deformities, pain, and functional losses persist, necessitating surgical interventions. This study evaluates the outcomes of hand surgeries in rheumatologic diseases, focusing on functional improvements, pain relief, and patient satisfaction. Materials and Methods: A retrospective analysis was conducted on 17 patients with confirmed rheumatologic diagnoses, including RA, systemic lupus erythematosus, scleroderma, and ankylosing spondylitis, who underwent hand surgeries between 2021 and 2024. Functional outcomes were assessed using the sequential occupational dexterity assessment (SODA) and Duruoz Scale, along with grip strength and pain levels measured using a visual analog scale (VAS). Complications, postoperative erythrocyte sedimentation rate (ESR), and patient satisfaction were also evaluated. Results: Soft tissue surgeries (79.2%) were more prevalent than bone surgeries (20.8%). Significant improvements were observed in functional outcomes (SODA and Duruoz Scores), grip strength, and VAS scores for general and hand-specific pain. However, ESR values remained unchanged, indicating persistent systemic inflammation. Complications occurred in 23.5% of patients, including infections, tendon adhesions, and recurrence of deformities. Patient satisfaction scores were moderate, highlighting unmet expectations. Conclusion: Hand surgeries provide substantial functional and pain-related benefits for patients with rheumatologic diseases, but moderate satisfaction levels and high complication rates underscore the need for better preoperative counseling, implant accessibility, and multidisciplinary management. Future studies with larger cohorts are warranted to refine surgical approaches and improve outcomes.